ANALISIS EXPERIENTIAL MARKETING, PERCEIVED QUALITY DAN ADVERTISING TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK KOPI GOOD DAY CAPPUCCINO - Ita Rahmawati; Imamatus Nisma Nur Hidayah (Jurnal Inovasi Penelitian, 2021)
The purpose of this study is to analyze experiential marketing, perceived quality and advertising on purchasing decisions on Good Day Cappuccino coffee products. The data used in this study is primary data where the data was obtained from the University of KH. A. Wahab Hasbullah. The sampling technique used the Stratified Random Sampling method, then the data was processed using multiple regression analysis. Samples were taken of 129 people from a total population of 190 respondents. The data collection used in this study is a questionnaire, where each class is given several samples that have been calculated using the Stratified Random Sampling method. After testing the hypothesis, it can be seen that in the partial test it can be seen that the experiential marketing, perceived quality and advertising variables have a significant level less than 0.05, meaning that these three variables have a relationship with the purchasing decision variable. While simultaneously there is a significant 0.000 less than 0.05, then Ho is rejected, Ha is accepted, meaning that there is a relationship between experiential marketing variables, perceived quality and advertising on purchasing decision variables.